Gender Issues in Taekwondo - Njegovan, Jovana (Sport - nauka i praksa, 2025)
The aim of this research was to examine the impact of gender issues on the experiences of male and female athletes in taekwondo, with a special focus on the perception of equality, stereotypes about martial arts, as well as challenges and opportunities for athlete development regardless of gender. The research sample included thirty taekwondo practitioners of both genders from the Taekwondo Federation of Bosnia and Herzegovina, representing five different clubs. The study was conducted using a qualitative approach, applying the in-depth interview technique. Based on qualitative coding methods, the final version of the coding tree identified three areas and five categories, with corresponding dimensions of gender issues in taekwondo. The research showed that gender equality and stereotypes in taekwondo are complex and dynamic issues. Although progress has been made in perception and practice, stereotypes still partially influence athletes' experiences, especially those of female athletes. The results indicate that family and community play a crucial role in overcoming these obstacles, while institutional investments and continuous education can further contribute to improving gender equality in this sport.
Keywords: aspects of equality; competitors; martial arts